1989
DOI: 10.5271/sjweh.1855
|View full text |Cite
|
Sign up to set email alerts
|

Radiographically detectable lumbar degenerative changes as risk indicators of back pain. A cross-sectional epidemiologic study of concrete reinforcement workers and house painters.

Abstract: RllHIMAKI II, WICKSTROM G, HANNINEN K, MATTSSON T, WARIS P, ZITIING A. Radiographically detectable lumbar degenerative changes as risk indicators of back pain: a cross-sectional epidemiologic study of concrete reinforcement workers and house painters. Scand J Work Environ Health 1989;15:280-285. The association between radiographically detectable degenerative changes in the lumbar spine and back symptoms was studied, along with the possible effect of occupational work load. The subjects were 216 concrete reinf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
4

Year Published

1991
1991
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 24 publications
0
19
0
4
Order By: Relevance
“…One recent study of construction workers reported that progressive degenerative spinal changes were associated with an increased risk of sciatic pain (38,39).…”
Section: Discussionmentioning
confidence: 99%
“…One recent study of construction workers reported that progressive degenerative spinal changes were associated with an increased risk of sciatic pain (38,39).…”
Section: Discussionmentioning
confidence: 99%
“…The occupation-based populations' unadjusted association for disc space narrowing ranged from a uOR of 1.23 (95% CI: 0.48-3.15) to 2.47 (95% CI: 1.10-5.56) [52,55]. The uOR of osteophytes ranged from 1.38 (95% CI: 0.94-2.05) to 3.00 (95% CI: 1.23-7.33) [52,53]. Spondylolisthesis associations ranged from a uOR of 1.54 (95% CI: 0.60-3.95) to 2.43 (95% CI: 1.40-4.22) [51,56].…”
Section: Search and Selection Of Studiesmentioning
confidence: 98%
“…The most frequently investigated radiographic finding was disc space narrowing (N ¼ 14), while facet joint osteoarthritis was the least studied (N ¼ 2). Six studies were occupation-based, including 3182 male subjects (no females were included in these studies) [51][52][53][54][55][56]. The mean weight ranged from 67.4 to 77.3 kg, and the mean age ranged from 18 to 42 years.…”
Section: Search and Selection Of Studiesmentioning
confidence: 99%
“…My co-workers and I (23) found that degeneration of the lumbar spine is associated with sciatic pain but not with lumbago or nonspecific back pain. Comparison of these studies is difficult because the classification of radiographic findings varies from one study to another.…”
Section: Origin Of Low-back Painmentioning
confidence: 98%